+0  
 
0
118
4
avatar+1195 

If \(f(x)=g(g(x))-g(x)\) and g(x)=2x-1 find f(3).

 
 Oct 8, 2019
 #1
avatar+106539 
+2

f(x)  =  g (g(x))

 

g (g (x))    means that we sub g(x) into itself....so we have that

 

g(g(x) ) = 2 (2x - 1) - 1  =

 

4x - 2 - 1  =

 

4x - 3

 

So....since this is  f(x)

 

Then f(3)  =

 

4(3)  - 3  =

 

12 - 3  =

 

9

 

 

cool cool cool

 Oct 9, 2019
 #2
avatar+1195 
+1

I am using AoPs when I typed in 9 as the ansswer it said it was incorrect

 Oct 9, 2019
 #3
avatar+19879 
0

Chris just forgot the -g(x) portion of f(x)

 

 

so he got 9 fpr the first part...

 

9 - (2(3)-1)

9-6+1 = 4

 Oct 9, 2019
 #4
avatar+106539 
+1

OOPS!!!....thanks, EP!!!

 

 

cool cool cool

CPhill  Oct 9, 2019

33 Online Users

avatar
avatar
avatar